EVALUATION OF GENERATION AND TRANSMISSION ASSETS ON NODAL PRICES IN ELECTRICITY MARKET - Pramod Gadge; Prakash Burade; Deepak Kadam (Proceedings on Engineering Sciences, 2023)
Electric utilities are going through a phase of quick changes, especially in the marketplace and rigid policies. Under such circumstances, electricity carrying prices can profile the level of contest in the electricity marketplace. Nodal pricing in such circumstances is one of the valuable schemes to reach transmission pricing goals. The performance of the Electricity Act 2003 has started the entry of the general electricity market in the Indian electricity sector. The implementation of the Transmission Open Access (TOA) regulation in India aims to confirm the required infrastructure and appropriate pricing strategies to support competition in this market. This study seeks to: (1) address the transmission pricing concerns that are prevalent and Nodal pricing that is exacting; (2) formulate the most advantageous Nodal price; and (3) implement the Nodal pricing methodology via IEEE-57. (4) to examine how transmission and generating assets affect nodal prices. Paper finalized that Nodal pricing is easy to execute over real network conditions and precious in achieving transmission pricing objectives.